Observational study on the potential psychological factors that affected Italian nurses involved in the COVID-19 health emergency : Nurses’ psychological factors during COVID-19 health emergency - Vitale, Elsa; Galatola, Vito; Mea, Rocco (Acta Biomedica Atenei Parmensis, 2021)
Background and Aim of the work. The present study aimed to identify the potential psychological malaise factors affecting the Italian nurses on the front lines of Covid-19 patient care since evidence suggested that they are at high risk of developing psychological disorders. Methods. An online questionnaire was administered to 291 Italian nurses, containing information on: sex, years of work experience, region of Italy where nurses worked and the intensive care unit assignment. Then, the anxiety disorders, the impact of the event, the depression and the insomnia conditions and their principal psychological factors influencing nurses during the health emergency. were assessed Results. Nurses worked in Northern Italy registered higher anxiety scores than others (p=0.023); the assignment to the intensive care unit (p=0.042) not influenced these scores. The total impact of event (IES-R) values ​​evidenced that women recorded higher “Avoidance” (p=0.032) and “Hyperarousal” (p=0.003) values ​​than men. The nurses who worked in Northern Italy recorded higher scores of “Hyperarousal” (p=0.010) and IES-R total (p=0.044). More women than men showed insomnia conditions (p=0.038) and nurses with a number of years of work experience not exceeding 10 years recorded greater levels of depression than the others (p=0.031). The psychological factors affected nurses included: the “Pleasure/Interest” dimension which correlated with the “Uncontrollable Thinking” (p=0.007), the “Unsatisfactory sleep/wake rhythm” (p=0.004), and the “Unmanageable pain and weakness” (p=0.001). Conclusions. Urgent need to intervene with psychological support programs for health professionals, such as nurses who are facing the health emergency from Covid-19 on the front line.